Relevansi Nilai-Nilai Kearifan Lokal Dalam Pembentukan Santri Yang Moderat - Yumnah, Siti (Proceedings of Annual Conference for Muslim Scholars, 2023)
This research aims to explain and identify the relevance of local wisdom values in the process of forming moderate santri character. Education in Islamic boarding schools, as traditional Islamic educational institutions, has a very important role in shaping the character of students. This article discusses the importance of understanding local wisdom values and how these values can contribute to producing students who have moderate character. The research method used is literature study or literature study. The research results show that local wisdom values such as mutual cooperation, local wisdom and social norms have a strong relevance in forming the moderate character of santri. These values help students develop attitudes of tolerance, independence and a sense of responsibility. This article also outlines several efforts that can be made by Islamic boarding schools and educators to strengthen the role of local wisdom values in Islamic boarding school education. By combining moderate Islamic teachings and local wisdom values, Islamic boarding schools can become effective educational institutions in shaping the character of students who are moderate and contribute positively to society